Failure Characteristics of Wet-Clutches in Limited Slip Differentials - Schneider, Thomas; Völkel, Katharina; Stahl, Karsten (VDI Verlag GMBH, 2023)
Wet multi-plate clutches are used in modern automotive powertrains to perform essential roles in terms of function, safety, and comfort. For example, in heavy as well as sporty vehicles, wet clutches are used in transient slip operation in limited-slip differentials and torque vectoring systems to improve lateral dynamics. Meanwhile, increasing torques in vehicles with internal combustion engines and especially in electric cars, have increased the power density in transmissions over the last decades [1]. Consequently, wet multi-plate clutches must also transmit more power in a comparable installation space without worsening service life, loss behavior, and shifting comfort. Failure of wet-running clutches in vehicle transmission applications is almost invariably critical to safety, as it can lead to driving incapacitation. Of particular concern are spontaneous failures, which can lead to clutch failure during one shifting process and are therefore not detectable in advance [2]. In this paper, the first step is to present a test method for investigating the spontaneous damage behavior of wet-running clutches in transient operation. Based on this, three different friction plates (paper friction plate, composite carbon friction plate, woven carbon friction plate) are investigated concerning damage behavior. The investigations show that with Friction System 1 and Friction System 2, discoloration initially occurs on the steel and lining plate. In the further course of the step tests, the discoloration increases. The failure of Friction Systems 1 and 2 is due to the buckling of the steel plates. Topography measurements show that the axial deformation of the steel plates is up to 2.4 mm. In the case of Friction System 3, there is no up to slight discoloration of the steel and lining plate. The cause of failure is the detachment of the friction lining from the carrier plate. For all three friction systems, it can be determined that the damage intensity is most pronounced in the center of the clutch and that temperatures above 300°C are necessary for the clutches to fail.
CRIS-Team Scopus Importer:2025-05-19